2016
DOI: 10.17245/jdapm.2016.16.3.203
|View full text |Cite
|
Sign up to set email alerts
|

A survey of dental treatment under general anesthesia in a Korean university hospital pediatric dental clinic

Abstract: BackgroundIn South Korea, the number of cases of dental treatment for the disabled is gradually increasing, primarily at regional dental clinics for the disabled. This study investigated pediatric patients at a treatment clinic for the disabled within a university hospital who received dental treatment under general anesthesia. This data could assist those that provide dental treatment for the disabled and guide future treatment directions and new policies.MethodsThis study was a retrospective analysis of 263 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
2
4
1
2
Order By: Relevance
“…In contrast to this study, Turkish study 15 all the dental procedures are finished at a mean of slightly more than 60 minutes. A recent Korean study 16 reported that the mean duration of treatment was 101 min, almost in agreement with the present study findings. Shin and co-workers 16 opined GA probably requires long treatment, is preferable to multiple sedation procedures in terms of both time and cost, and allows treatment to be completed in one visit without any psychological stress of treatment under restraint.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to this study, Turkish study 15 all the dental procedures are finished at a mean of slightly more than 60 minutes. A recent Korean study 16 reported that the mean duration of treatment was 101 min, almost in agreement with the present study findings. Shin and co-workers 16 opined GA probably requires long treatment, is preferable to multiple sedation procedures in terms of both time and cost, and allows treatment to be completed in one visit without any psychological stress of treatment under restraint.…”
Section: Discussionsupporting
confidence: 93%
“…Conscious sedation was the goal of a level of sedation, since the patient can respond to any verbal or tactile stimulus; However, in the case of patients with disabilities who have low levels of cooperation and high levels of anxiety, this type of conscious sedation has a lower success rate [10]. Therefore, the use of deep sedation or general anesthesia in these patients is more suitable for performing dental procedures, therefore, for the selection of which kind anesthetic technic perform we should be taken the risk-benefit factor [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some indications for general anesthesia where in-office services cannot be conducted (3,4). On the other hand, there has always been an attempt to use the technology of the day in pediatric dentistry.…”
Section: Dear Editormentioning
confidence: 99%